Factors associated with health behaviors in preventing non-communicable diseases among older adults living alone in poverty in Japan - Imamatsu, Yuki; Tadaka, Etsuko (Frontiers in Public Health, 2023)
Introduction Older adults who live alone in poverty are highly susceptible to non-communicable diseases and other adverse conditions owing to health disparities resulting from social structures. However, the factors associated with health behavior to prevent non-communicable diseases in this population are rarely explored.The purpose of this study was to identify factors associated with health behavior to prevent non-communicable diseases among older adults living alone in poverty. Methods We conducted a self-administered mail survey covering 2818 older adults living alone who were receiving public assistance, randomly selected from lists of individuals receiving national public assistance in all 1250 local social welfare offices across Japan. A total of 1608 individuals completed the questionnaire, a valid response rate of 57.1%. Respondents' mean age was 74.5 years (standard deviation = 6.7), and 52.9% were women. The study variables included demographic characteristics, scores on a health behavior scale for older adults living alone and receiving public assistance (HBSO), and individual and community-related factors. Results Logistic regression analysis revealed that the individual factor of having a health check-up in the past 12 months (odds ratio [OR]: 1.45, 95% confidence interval [CI]: 1.10-1.91) and the community-related factors Lubben social network scale score (OR 1.15, 95% CI: 1.12-1.18) and Community Commitment Scale score (OR: 1.04, 95% CI: 1.00-1.08) were significantly associated with HBSO scores. Conclusions To improve health behavior among older adults living alone in poverty in Japan, social structures, such as lowering mental barriers to the detection, treatment, and management of non-communicable diseases and developing human resources, should be changed to provide social support, such that these individuals are not only dependent on family and friends.